Long-term Postoperative Follow-up in Patients with Apparently Benign Pheochromocytoma and Paraganglioma - Amar, L.; Fassnacht, M.; Gimenez-Roqueplo, A.-P.; Januszewicz, A.; Prejbisz, A.; Timmers, H.; Plouin, P.-F. (Hormone and Metabolic Research, 2012)
Patients with pheochromocytoma or paraganglioma are at risk of developing tumor recurrences or new tumors after successful resection of the primary tumor. This review summarizes current knowledge concerning the incidence and risk factors for such events. The overall incidence exceeds 15%. Patients with inherited tumors have a higher probability of recurrence or new tumors. Most recurrences are metastatic, particularly in patients with SDHB mutations or nonhereditary tumors. We recommend the determination of plasma or urinary metanephrines (normetanephrine and metanephrine) 1 month after surgery. In patients with sporadic, single tumors≤5 cm in diameter, clinical and biochemical follow-up should be performed every 2 years. However, this follow-up period can be reduced to yearly, if it is more simple and more convenient for patients and physicians. Patients with larger or multiple but apparently benign tumors and/or inherited disease should be tested 6 months after surgery and then every year for the rest of their lives. Imaging follow-up is also required in patients with inherited or malignant tumors.
Keywords: genetics; malignant; metanephrines